2013
DOI: 10.1016/j.ajpath.2012.12.024
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-Induced Lung Injury Is Mitigated by Blockade of Gastrin-Releasing Peptide

Abstract: Gastrin-releasing peptide (GRP), secreted by pulmonary neuroendocrine cells, mediates oxidant-induced lung injury in animal models. Considering that GRP blockade abrogates pulmonary inflammation and fibrosis in hyperoxic baboons, we hypothesized that ionizing radiation triggers GRP secretion, contributing to inflammatory and fibrotic phases of radiation-induced lung injury (RiLI). Using C57BL/6 mouse model of pulmonary fibrosis developing ≥20 weeks after high-dose thoracic radiation (15 Gy), we injected small … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 51 publications
0
23
0
Order By: Relevance
“…In another study, hyperplasia of PNECs, increased nuclear p-Smad2/3 immunoreactivity, induced α-SMA expression and interstitial collagen accumulation were observed in the 6th, 10th and 20th weeks following the administration of high-dose of thoracic radiation to murine lungs. The administrations of GRP antagonist to mice (1 h after radiation exposure on the 20th week) resulted in the regression of these alterations [16]. Although this last study showed that GRP might modulate the pathogenesis of pulmonary fibrosis, the target cells and signalling pathways of GRP-mediated generation of fibrotic response were not investigated.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…In another study, hyperplasia of PNECs, increased nuclear p-Smad2/3 immunoreactivity, induced α-SMA expression and interstitial collagen accumulation were observed in the 6th, 10th and 20th weeks following the administration of high-dose of thoracic radiation to murine lungs. The administrations of GRP antagonist to mice (1 h after radiation exposure on the 20th week) resulted in the regression of these alterations [16]. Although this last study showed that GRP might modulate the pathogenesis of pulmonary fibrosis, the target cells and signalling pathways of GRP-mediated generation of fibrotic response were not investigated.…”
Section: Discussionmentioning
confidence: 88%
“…These alterations in the pathway resulted in a fibrotic response in the lung, by increasing the expression of α-SMA and procollagen-1 genes. Although there is no direct evidence that GRP stimulates TGF-β signalling pathway, Zhou and colleagues showed that the radiation induced fibrosis by increasing the number of p-Smad2/3 immunoreactive cells in the lungs of mice and the administration of GRP inhibitor regressed the pulmonary fibrosis by decreasing the number of p-Smad2/3 in the lungs [16]. The present study reveals that GRP stimulates Smad3-dependent TGF-β1 signalling, by increasing the expressions of SMAD3 and SMAD4 mRNAs, total Smad2/3, p-Smad2/ 3 and Smad4 proteins and reducing the expression of SMAD7 mRNA in MRC5 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[25] The most widely accepted pathophysiologic mechanism underlying the development of peribronchiolar fibrosis and constrictive bronchiolitis in DIPNECH is that bioactive substances (e.g., bombesin) secreted in larger-than-normal amount by the hyperplastic PNECs exert pro-fibrotic and pro-inflammatory effects on the adjacent airways. [8,26] , [27] This hypothesis triggered some physicians to propose two plausible therapeutic approaches to DIPNECH: 1) using SSAs to decrease the secretion of bioactive substances from the hyperplastic PNECs, [10,28] and 2) using steroids (inhaled and/or systemic) to control inflammation and prevent further parenchymal and airway damage. [13] Nassar et al summarized 25 cases of DIPNECH reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…Using a well-characterized mouse model of PF developing ~20 weeks after high-dose thoracic RT (15 Gy) (104), we injected GRP blocking small molecule 77427 1 h after RT then twice weekly for up to 20 weeks (8). Mice given RT plus PBS had increased interstitial CD68 + macrophages 4 weeks later and increased GRP + /PGP9.5 + PNECs 6 weeks later.…”
Section: Grp and Radiation-induced Pulmonary Fibrosismentioning
confidence: 99%